2015
DOI: 10.1007/s10803-015-2555-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Age of Diagnosis for Children with Autism Spectrum Disorder: The Role of a Consistent Source of Medical Care, Race, and Condition Severity

Abstract: Having a consistent source of medical care may facilitate diagnosis of autism spectrum disorders (ASD). This study examined predictors of age of ASD diagnosis using data from the 2011-2012 National Survey of Children's Health. Using multiple linear regression analysis, age of diagnosis was predicted by race, ASD severity, having a consistent source of care (CSC), and the interaction between these variables after controlling for birth cohort, birth order, poverty level, parental education, and health insurance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 74 publications
3
44
0
2
Order By: Relevance
“…A study of children from the Autism and Developmental Disabilities Monitoring Network found the median age of ASD diagnosis in the United States to be 52 months [Baio et al, ], but the fact that the presence of specific COCs can inadvertently increase or decrease the age at which ASD is first diagnosed [Soke et al, ] suggests that the relationships between COCs and ASD are still poorly understood. Demographic and socioeconomic factors can also influence the timing of diagnosis, although these account for a relatively small portion of the variation [Herlihy et al, ; Emerson, Morrell, & Neece, ]. An improved understanding of COC trajectories in young children may hold potential for more informed and consistently timed ASD diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…A study of children from the Autism and Developmental Disabilities Monitoring Network found the median age of ASD diagnosis in the United States to be 52 months [Baio et al, ], but the fact that the presence of specific COCs can inadvertently increase or decrease the age at which ASD is first diagnosed [Soke et al, ] suggests that the relationships between COCs and ASD are still poorly understood. Demographic and socioeconomic factors can also influence the timing of diagnosis, although these account for a relatively small portion of the variation [Herlihy et al, ; Emerson, Morrell, & Neece, ]. An improved understanding of COC trajectories in young children may hold potential for more informed and consistently timed ASD diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these strengths, the pediatric healthcare system is moving toward greater involvement of parents in the process of identifying early developmental delays (Feldman et al, 2005; Nordahl-Hansen, Kaale & Ulvund, 2013). Specifically, routine developmental screening via parent report is increasingly being used to identify at risk children, in accordance with American Academy of Pediatrics recommendations (Emerson, Morrell, & Neece, 2016; Johnson & Myers, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Studies from the United States have found earlier diagnosis age with higher parental education level and income [Mazurek et al, ; Thomas et al, ]. While non‐Hispanic Blacks in the United States were found to have an earlier diagnosis age when compared to Hispanics and non‐Hispanic Whites, this effect was limited to low severity ASD cases [Emerson, Morrell, & Neece, ; Jo et al, ]. To the best of our knowledge, there is no literature outlining diagnosis age in Israel according to sociodemographic factors.…”
Section: Introductionmentioning
confidence: 99%